APLIKASI NUTRINEEDS DALAM PENENTUAN KEBUTUHAN KALORI HARIAN BAGI PENDERITA DIABETES MELITUS - Siti Ayu Oktavianti; Yoga Divayana; I Gusti Agung Putu Raka Agung (Jurnal SPEKTRUM, 2021)
In this journal, an analysis of the NutriNeeds application is carried out. The Nutrineedsapplication is the result of a study that aims to determine daily calorie needs for people withdiabetes mellitus. The level of accuracy of the NutriNeeds application will be compared with theBroca method in determining the daily calorie requirements for people with diabetes mellitus.The NutriNeeds application is designed with the mamdani fuzzy inference system and androidstudio, which uses 7 inputs in the fuzzy inference system, namely gender, male BBI, femaleBBI, age, BMI, physical activity, stress factors, and produces an output, namely calories daily.The NutriNeeds application requires data input, namely gender, weight, height, age, andphysical activity, which will display daily calorie results and meal schedules. The data in thisstudy were 5 pieces of data on patients with diabetes mellitus. Based on the comparison of dailycalories generated by the NutriNeeds application by calculating daily calories using the Brocamethod, the results of the calculation of the percentage of accuracy obtained a MAPE value ofthe NutriNeeds application of 1.1% which is classified as very accurate.